Correlation analysis of texture and chemical properties of olecranon honey peach cultivars from different provinces in China - Qiu, Yuanxin; Zhu, Kaiqi; Liu, Jianliang (Emirates Journal of Food and Agriculture, 2022)
Texture is key to the fruit quality for the olecranon honey peach. In this study, olecranon honey peach was harvested from 11 Chinese Provinces and the effect of the olecranon honey peach planting areas on fruit texture and the relationship between texture and chemical parameters was investigated. In the texture section, peaches were measured by texture profile analysis (TPA) and puncture tests. Predictive models were developed to determine the texture of olecranon honey peach based on chemical properties. The results demonstrated that olecranon honey peach grown in Lianping county had significantly better texture and structure than those grown in other locations, especially the peach which planted in Lianping county with the 4.0 planting technology at high altitude. Correlation results showed that the texture of olecranon honey peach was negatively correlated with water content, while the hardness of texture parameters was positively correlated with pectin content and crispness was negatively correlated with titratable acid. Creating texture models that can estimate the texture value of olecranon honey peach by water content, pectin, and titratable acid